Liberation Theology in Indonesia: The Role of Cak Nun and Maiyah Community in Social Transformation - Chrisanto, Ilyas Alhafid (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
This article aims to examine the application of liberation theology in Indonesian Islam, focusing on the efforts of Muhammad Ainun Nadjib (Cak Nun) and the Maiyah Community Assembly, analyzed through Ali Shari’ati's concept of rausyanfikr. The study aims to explore how Cak Nun contextualizes Islam to address contemporary issues of injustice, oppression, and social alienation. Utilizing qualitative library research methods, it investigates various literary sources to evaluate the role of Islamic teachings in cultural and social emancipation. Findings indicate that Cak Nun and the Maiyah Community Assembly have played crucial roles in heightening community awareness about prevalent oppression, employing the Quran and Islamic thought as tools for liberation. The study concludes that Islam, as interpreted by Cak Nun, serves as an effective means for societal change, promoting a comprehensive application of Islamic teachings to address modern societal challenges. This research holds significant implications for scholars and practitioners interested in the intersections of religion and social transformation.